Analisis Proksimat Dan Skrining Fitokimia Tumbuhan Di Perairan Pantai Sekilak Kota Batam - Hesti Marliza; Suci Fitriani Sammulia; Delladari Mayefis (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2023)
Riau Islands is one of the provinces in Indonesia that has abundant biodiversity. Biodiversity is the basis of various treatments and industrial discoveries in the pharmaceutical field in the future, people especially in developing countries depen on plants as medical ingredients to maintain their health. Therefore, efforts are needed to determine the content of primary and secondary metabolites obtained through proximate analysis and phytochemical screening test in plants. This study aims to explore and document the content of plant compounds on the Sekilak beach, Batam City. Amphiroa fragilissima was positive contained flavonoids, steroids, and saponins, water content 36,31%, ash content 44,09%, protein content 3,21%, fat content 8% and carbohydrate content 8,39%. Halimeda opuntia positive contained flavonoids compunds, alkaloids, and water content 27,68%, ash content 33,70%, fat content 7%, protein content 0,25%, and carbohydrate contain 31,37%. Halimeda macroloba positive contains flavonoids compounds, steroids, saponins, and water content 53,17%, ash content 13,26%, fat content 6%, protein content 1,00%, and carbohydrate content 26,57%.